Antibacterial potential of fungal endophytes from selected seaweeds from Johor Coast - Muhammad Haziq Anwar Azlan; Nur Farah Ain Zainee; Nazlina Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Endophytic fungi from marine seaweed have been known to be the source of new secondary biological metabolites. The ample coast in Malaysia in particular the Johor Coast has diverse marine seaweed, home to potential marine endophytic fungi. In this light, this study aims to characterise endophytic fungi in selected seaweeds from the Johor Coast and determine the antibacterial potential. Fungal endophytes were aseptically isolated from brown seaweed, Sargassum sp. and green algae, Ulva lactuca. Macroscopic and microscopic observations were performed for characterisation as fungal genera. Sequence analysis of Internal Transcribed Spacer (ITS) suggested the five fungal isolates as Trichoderma asperellum, Aspergillus aculeatus, Aspergillus fumigatus, Penicillium sp. FKI-3389 and Hypoxylon monticulosum. Antibacterial activity was determined by minimum inhibition concentration assay against five human pathogenic bacteria. Only T. asperellum, A. fumigatus and H. monticulosum showed antibacterial potential with the latter indicating broad-spectrum antibacterial activity. As a conclusion, five endophytic fungal species were successfully determined from the brown and green seaweeds. Three of the fungal endophytes showed potential in antibacterial activity with H. monticulosum displayed broad spectrum activity.